The Suitability Index of Mangrove Tourism in the Coastal Area around Budo Village, Wori Sub-District, North Minahasa Regency for Marine Ecotourism - Tambunan, Rose Agustin; Rumengan, Antonius Petrus; Paruntu, Carolus Paulus; Rampengan, Royke M.; Ompi, Medy; Rompas, Rizald Max (Sam Ratulangi University, 2023)
The purpose of this study was to analyze the tourism suitability index and the carrying capacity of the mangrove ecotourism area in Budo Village, Wori District, North Minahasa Regency. The research method used was a cruising survey method using line transects and visual method which were carried out on three transects to obtain mangrove bio-ecological parameter values, namely thickness, species, density, biota objects associated with mangroves, and sea tides. The results showed that the mangrove thickness values ​​on transects 1-3 were 157 m, 138 m, and 135 m respectively, with an average value of 143.3 m; a number of mangrove species, namely 6 species (Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, Sonneratia alba, Avicennia marina, and Nypa fruticans); mangrove density values ​​on transects 1-3, respectively 10.2 ind/100 m2, 11.8 ind/100 m2 and 6.2 ind/100 m2, with an average value of 9.4 ind/100 m2; mangrove association biota objects in transects 1-3, including fishes, shrimps, crabs, mollusks, birds and reptiles; and the average tidal value is as high as 2 m. The average value of the tourism suitability index was 54.6% with the conditionally appropriate category on all transects; and the carrying capacity of the mangrove tourism area was 116 people/day, with an operational time of 14 hours/day. Further research requires a sustainability analysis to produce efficient and effective programs for the development of mangrove ecotourism in Budo Village. Keywords: Area carrying capacity, Budo Village, Ecotourism, Tourism suitability index, Mangrove Abstrak Tujuan dari penelitian ini untuk menganalisis indeks kesesuaian wisata dan daya dukung kawasan ekowisata mangrove Desa Budo, Kecamatan Wori, Kabupaten Minahasa Utara. Metode penelitian yang digunakan adalah metode survei jelajah dengan menggunakan line transect dan metode visual pada tiga transek untuk memperoleh nilai-nilai parameter bio-ekologi mangrove, yaitu ketebalan, jenis, kerapatan jenis, objek biota asosiasi mangrove, dan pasang surut air laut. Hasil penelitian menunjukan bahwa nilai ketebalan mangrove pada transek 1-3, masing-masing adalah 157 m, 138 m, dan 135 m, dengan nilai rata-ratanya 143,3 m; jumlah jenis mangrove 6 spesies (Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, Sonneratia alba, Avicennia marina dan Nypa fruticans); nilai kerapatan mangrove pada transek 1-3, masing-masing adalah 10,2 ind/100 m2, 11,8 ind/100 m2 dan 6,2 ind/100 m2, dengan nilai rata-ratanya 9,4 ind/100 m2; objek biota asosiasi mangrove pada transek 1-3 meliputi ikan, udang, kepiting, moluska, burung, dan reptil; dan nilai rata-rata pasang surut air laut setinggi 2 m; nilai rata-rata Indeks kesesuaian wisata sebesar 54,6 % dengan kategori “sesuai bersyarat” pada semua transek; dan daya dukung kawasan wisata mangrove Desa Budo adalah 116 orang/hari dengan waktu operasional 14 jam/hari. Penelitian selanjutnya diperlukan analisis keberlanjutan untuk menghasilkan program-program yang efisien dan efektif dalam rangka pengembangan ekowisata mangrove Desa Budo. Kata kunci: Daya dukung kawasan, Desa Budo, Ekowisata, Indeks kesesuaian wisata, Mangrove